Black Caregiver Perspectives During a Developmental Diagnostic Interview. - Thompson Brown, Lillian; Kasambira Fannin, Danai; Lamptey, Ann; Uzonyi, Thelma E.; Pearson, Jamie N. (Journal of Autism & Developmental Disorders, 2026)
Despite increasing autism prevalence rates across racial and ethnic groups, research has traditionally overlooked the influence of culture on developmental diagnostic conversations. Addressing this gap in research is crucial to understanding and mitigating potential disparities in diagnostic experiences, especially among Black caregivers. Black caregivers encounter frustration and discrimination during the diagnostic process, citing dismissiveness and a lack of cultural competence from healthcare providers. To address these issues, this study centers the perspectives of Black caregivers as they participate in a developmental diagnostic program for toddlers under three years of age. This retrospective qualitative study, conducted exclusively by a Black research team, involved nineteen Black caregivers of thirteen toddlers as they participated in semi-structured interviews conducted by a multidisciplinary clinical team. The research team employed a conceptual content analysis to examine caregivers' descriptions of their children's behaviors and characteristics, as well as the factors and experiences associated with their descriptions. Caregivers provided distinct descriptions of behaviors and characteristics in the categories of language and communication, learning, and temperament, associating them with situational and dispositional factors and experiences. The findings offer valuable insights for implementing culturally responsive diagnostic practices. Additionally, these results may enhance the quality of caregiver-provider interactions during developmental assessment, leading to earlier and more accurate diagnoses for Black children.